2018
DOI: 10.4022/jafib.1726
|View full text |Cite
|
Sign up to set email alerts
|

Early Recurrences During The Blanking Period After Atrial Fibrillation Ablation

Abstract: Early recurrences of atrial arrhythmias (ERAA) after ablation are common and predict late recurrences and ablation failure.However,becausea proportion of patients with ERAA will have no subsequent arrhythmias after the blanking period, consensus guidelines recommend against immediate repeat ablation for ERAA episodes occurring during the first 3 months post-ablation. In this review, we summarize the predictors, significance, and treatment of ERAA after AF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
4
7
0
1
Order By: Relevance
“…In agreement with other studies, we found that early recurrence was a strong predictor for recurrence during the later months . Therefore, detection of early recurrence has clinical prognostic value and could aid in tailoring treatment plans and determining when an ablation should be considered successful, or if repeat ablation and continued anticoagulation is required.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In agreement with other studies, we found that early recurrence was a strong predictor for recurrence during the later months . Therefore, detection of early recurrence has clinical prognostic value and could aid in tailoring treatment plans and determining when an ablation should be considered successful, or if repeat ablation and continued anticoagulation is required.…”
Section: Discussionsupporting
confidence: 91%
“…Early reablation has been shown to improve long-term freedom from AF. 23,26,27 In agreement with other studies, 28 we found that early recurrence was a strong predictor for recurrence during the later months. 23 Mobile heart monitor devices may be useful not only for their positive predictive value but also for their ability to eliminate false positives.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations